Isolation of beneficial bacteria and feed incorporated with beneficial bacteria on growth performance of asian sea bass (Lates calcarifer, bloch) fingerling - Tarry, Wendy Ferrina (2015)
The intestinal tract of healthy animals is assumed to be the natural place of ‘good’ micro-organisms. The present study investigated different parts of intestine of Asian sea bass (Lates calcarifer, Bloch) to isolate and identify strains potentially useful for fish probiotics. In vivo test was done to validate the performance of isolated Enterobacter ludwigii potential probiotic to be used in sea bass fry rearing in aquaculture industry. Five Randomized Complete Block Design (RCBD) treatments for different concentration of E. ludwigii were mixed with sea bass feed, i.e., T1 (control; without E. ludwigii), T2 (1×101 cfu/g of E. ludwigii), T3 (1×103 cfu/g of E. ludwigii), T4 (1×106 cfu/g of E. ludwigii), T5 (1×109 cfu/g of E. ludwigii) and fed to the sea bass fry for 28 days. The total culturable aerobic gut bacteria of both live and dead sea bass samples ranged from 1.17−84.00 × 106 cfu/g, with counts being higher in posterior intestine (1.97−84.00 × 106 cfu/g) compared to the number of cells occurring in anterior (0.21−7.87 × 106 cfu/g) and middle (1.17−3.50 × 106 cfu/g) parts, although significantly (p<0.05) higher numbers were associated with live fish. The isolate MS32 was selected that inhibit the growth of fish pathogens Vibrio parahaemolyticus and Aeromonas hydrophilla in disc diffusion, well diffusion assay and cross streak. The isolate MS32 produced gamma-hemolysin and was identified by standard biochemical tests and 16S rDNA sequences as E. ludwigii. The species E. ludwigii can be grouped as moderately halophile marine bacteria. Storage at 4oC is suitable to store sea bass feed pellet that have been mixed with E. ludwigii and can be used for about 20 days. In vitro test showed that E. ludwigii formed a clear inhibition zone against 3 fish pathogens at concentration level of 1×109 cfu/ml via well and disc diffusion method. Presence of E. ludwigii in feed was safe to be used to the sea bass fry where no significant difference (p>0.05) among treatments and control. E. ludwigii did not improved the growth or increased appetite of sea bass fry with no significant difference (p>0.05) on the growth performance of sea bass fry. The number of E. ludwigii in the gastrointestinal tract of sea bass fry and each water sample were also not significantly different (p>0.05). Significant difference (p<0.05) in nitrate, ammonium and phosphate concentrations of rearing water of sea bass fry was observed within the treatments. The concentration of nitrate range from 0.0012–0.0022 mg/L, phosphate concentration from 0.032–0.045 mg/L and ammonium concentrations from 0.981–1.457 mg/L. The presence of E. ludwigii can help to improve the water quality compared to control group. Observation after 7 days of challenge test against V. parahaemolyticus (2×108 cfu/ml) showed that the highest survival percentage (100%) was found for T5 compared to T1 (79%).The findings of the study revealed that E. ludwigii could be a potential probiotics for rearing of sea bass fry where improvement of water quality in the rearing tank of sea bass fry and protection against fish pathogen were remarkable.